Role of spirituality in health care: knowledge, attitude and practices amongst medical professionals in a tertiary care hospital - Bhat, K. Kriti; Yadavannavar, M. C. (International Journal Of Community Medicine And Public Health, 2016)
Background: Spirituality has been integral part of medicine and health since ancient age. The extent of spiritual component in medical practice in India is largely unknown. Therefore, the present study was undertaken to assess the extent of knowledge (awareness), attitude and practice among medical professionals regarding the role of spirituality in management of health. Objectives of the study were to study the knowledge, attitude and practices of spirituality in medical practice amongst medical professionals. Methods: A cross-sectional study was conducted in Shri B. M. Patil Medical College Hospital and Research Centre, Vijayapura from November 2015 to December 2015. 150 doctors of all specialties were interviewed using a self-reported multiple choice questionnaire, after obtaining informed consent. Information regarding demographic profile, knowledge, attitude and practices of spirituality in medical practice was collected. Analysis was done using percentages. Results: The response rate was 60% (150/250). More than 80% had a good deal of knowledge of spirituality but were unable to distinguish between spiritual practices and traditional religious rituals. 67% of them felt that spirituality may have resounding effects on psychiatric illnesses in adults. 75% of them practice spirituality in any form of self-health. Majority of the participants agreed that spirituality offers maximum health benefits in chronic diseases. Conclusions: It is evident from this study that there is a wide gap between reality and physician’s perception of spirituality. Concepts regarding spirituality and it’s application in health is lacking. Hence, redefining the place of spirituality in health and disease by way of conducting collaborative research by qualified and dedicated professionals is the need of the hour.